2020
DOI: 10.1038/s41598-020-75228-w
|View full text |Cite
|
Sign up to set email alerts
|

The association between thyroid function biomarkers and attention deficit hyperactivity disorder

Abstract: The relation between thyroid function biomarkers and attention deficit hyperactivity disorder (ADHD) in children and adolescents is currently unclear. Cross-sectional data from the German Health Interview and Examination Survey for Children and Adolescents (KiGGS Baseline) was analyzed to assess the association between thyroid function biomarkers and ADHD in a population-based, nationally representative sample. The study cohort included 11,588 children and adolescents with 572 and 559 having an ADHD diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…20 Another study has demonstrated that in children, but not in adolescents, increased serum TSH levels were associated with a decreased risk of ADHD diagnosis. 8 More recently, no significant correlation was found between serum TSH levels and the symptoms of ADHD in India. 21 This finding is not in concordance with our results.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…20 Another study has demonstrated that in children, but not in adolescents, increased serum TSH levels were associated with a decreased risk of ADHD diagnosis. 8 More recently, no significant correlation was found between serum TSH levels and the symptoms of ADHD in India. 21 This finding is not in concordance with our results.…”
Section: Discussionmentioning
confidence: 98%
“…7 Several lines of evidence indicate that fetal brain development may be harmed by maternal thyroid dysfunction. 8 Specifically, the risk of ADHD in the offspring is increased by maternal (overt) hyperthyroidism, 9,10 high TSH concentration during pregnancy, 11 and maternal autoimmune thyroiditis 12 in the early stages of pregnancy. More recently, it has been reported that in contrast to children without hyperthyroidism, the prevalence ratio of ADHD in children who have hyperthyroidism is 1.7.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these findings, we postulated that the SDQ score has utility in studies that focus on the risk of mental health, prior to an actual disease diagnosis. Along with our studies, the SDQ scores have also been used in earlier biomarker analyses to assess the risk of emotional and behavioral difficulties among children or adolescents [ 34 , 35 ]. Goodman and Goodman showed in their studies that children with higher total difficulty SDQ scores have greater psychopathology, which can be predictive of a disorder status three years later [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Small intrapersonal changes in thyroid function, within the normal reference range, have been linked to adverse health outcomes [5]. Furthermore, TH dysregulation or disease might also influence cognitive functions [6] and mental health, including dysregulated mood [7], depression [8, 9], behavior [10], and attention-deficit hyperactivity disorder in children [11, 12]. The most relevant mechanisms of thyroid dysfunction due to endocrine-disrupting chemicals are: disturbance of overall thyroid gland activity via interference with the TH or TSH receptors through stimulation, inhibition or interference with other receptors on the thyrocyte; stimulation or inhibition of the enzyme functions that mediate the thyroid gland iodine uptake in the synthesis of T3 and T4; and competitive displacement of THs on their binding protein [4].…”
Section: Introductionmentioning
confidence: 99%